Strategi Bank Muamalat Cabang Jember Dalam Meningkatkan Kualitas Pelayanan Dan Kepuasan Nasabah - Imaniyah, Nidaan Farhanin (UPT Penerbitan Universitas Jember, 2024)
This research aims to explore the strategy of Bank Muamalat Jember Branch in improving service quality and customer satisfaction. The research method used in this research is a qualitative descriptive approach with the data collection methods used are observation, interviews and documentation. The research results based on interviews stated that the strategies carried out by Bank Muamalat Jember Branch in improving service quality were in applying SERVQUAL (service quality), namely tangible, reliability, responsiveness, assurance and empathy; and strategies for increasing customer satisfaction by Bank Muamalat Jember Branch implementing customer measurement methods, namely a suggestion complaint system and customer satisfaction surveys.